Charge sharing scheme for electric vehicles based on battery monitoring - Vijayan, Abhilash T.; Dev, Jothish V.; Henry, Healsa (Institute of Advanced Engineering and Science, 2024)
The demand for electric vehicles (EVs) is rising due to the environmental impact of zero emission, high efficiency, and a deterioration in the levels of conventional fuels. Initial expense, the range, the time for charging and the availability of charging stations narrows their popularity. Alternately, smart approaches like vehicle-to-home (V2H), vehicle-to-vehicle (V2V), and vehicle-to-grid (V2G) charging schemes can modify this situation and shape the grid-side load curves. Vehicles in need can utilize V2V, where the transfer of charge between electric vehicles ensures the transit up to the nearby charging stations. There are wired and wireless modes in V2V topology. When equipped with the required switchgear, wireless power transfer (WPT) between electric vehicles offers great possibilities in charge sharing. A wireless charging system gives EV owner’s freedom of easy charging without waiting in a queue. This paper compares the performance and utilities of wired scheme and wireless scheme for power transfer between vehicles. Both the strategies check the state of charge (SoC) of the batteries and facilitate the power transfer. Simulations in MATLAB/Simulink and experimental results validate the proposed schemes.